Factor Analysis Correlating to The Increase of Voluntary Counseling and Testing (VCT) Visits of Pregnant Women At Papusungan Community Health Center - Kusmiyati; Tirtawati, Gusti Ayu; Dompas, Robin; Montolalu, Agnes; Lontaan, Anita; Tamarol, Janake E. (Journal of Health and Nutrition Research, 2023)
This research aimed to analyze the factors correlating to the increase of Voluntary Counseling and Testing (VCT) of pregnant women at Papusungan Community Health Center, Bitung City. The research type used was analytic observation research design and cross-sectional approach carried out on 70 pregnant women resided in work area of Papusungan Community Health Center with research instrument was in the form of a questionnaire consisted of 10 knowledge questions, 20 questions on the role of medical staff and 6 questions about the motivation of pregnant women. Data analysis used chi square test with meaning value 95% (0.05). Knowledge: the respondents with less knowledge about VCT were 53.4% (37 out of total 70 respondents), the respondents stated that the medical staff role was good with amount 58,6% (41 out of 70 respondents), and the respondents with good motivation was 62,9% (44 out of total 70 respondents). Then, pregnant women who did VCT were 65.7% and those who did not do VCT was 34.3%. There is significant correlation between knowledge and the medical staff role to increase VCT visits of pregnant women, but there is no significant correlation between their motivation and the increase of VCT visit